Quantitative Assessment of Coronary plaques by coronary CT angiography: high inter-reader and intra-reader agreement is achieved by inter-scanner variablity should not be ignored - Sun, Zhonghua (Openventio, 2017)
This editorial discusses a recent paper published in the December issue of Radiology 2016 on the quantitative assessment of coronary plaques by coronary computed tomography (CT) angiography. Three main findings are discussed in the editorial: First, coronary CT angiography is an accurate imaging modality for analysis of plaque volume as well as monitoring volume change, with excellent inter- and intra-reader agreement with use of the state-of-the-art CT scanners. Second, the reliability of coronary CT angiography is noticed for low scan variability when plaque volume assessment is performed with the same vendor, but with high variability of nearly 30% when assessment is conducted with different vendors at baseline and follow-up scans. Finally, a large sample size is required to assess non-calcified plaques, in particular with use of different vendors.